What Is New in Classification, Diagnosis and Management of Chronic Musculoskeletal Pain: A Narrative Review - Zhuang, Jiejie; Mei, Houlian; Fang, Fang; Ma, Xiaqing (Frontiers in Pain Research, 2022)
Chronic musculoskeletal pain (CMP) is the most common type of chronic pain, defined as persistent or recurrent pain condition deriving from musculoskeletal structures such as muscles, joints or bones that lasts for more than 3 months. CMP is multifactorial and severely affects people’s quality of life. CMP may be influenced by a number of factors, including contextual factors, the presence of comorbidities, arthritis coping efficacy and access to CMP care. To deepen the comprehensive understanding of CMP, this narrative review provides the latest literature on disease classification, clinical diagnosis, treatment and basic research. In terms of the classification of the disease, here we introduce the 11th edition of the International Classification of Diseases (IDC-11), in which CMP is divided into chronic primary musculoskeletal pain and chronic secondary musculoskeletal pain. In the clinical diagnosis section, the progress of central sensitization in the diagnosis of CMP will also be summarized. In addition, we summarize some recent advances in clinical treatment and basic research.